FORMATION OF THE LANGUAGE CULTURE OF JUNIOR PUPILS IN A DIALECTICAL ENVIRONMENT: THEORETICAL AND PRACTICAL ASPECTS - Bilavych, Halyna; Pantyuk, Tetyana; Savchuk, Borys; Holovchak, Nataliya (Mountain School of Ukrainian Carpaty, 2018)
Language culture creation is one of the most urgent questions nowadays. This is not only philological problem, but social as well – as it is related to different communication methods.The article covers linguistic principles of language culture creation for pupils provided dialect environment. Proved that the necessary condition for high level language culture for future primary school teachers provided dialect environment is compliance principles of oral speaking: orthoepic, lexical, grammar, stylistic. The most important their properties are accuracy, cleanliness, purity etc.Also there is covered speech environment role in creating language culture of individual. We determine language culture for junior pupilsas possession of verbal and written forms of language on all levels, ability to use optimal language tools for current situation. Language norm is main concept of language culture. We believe that main requirement for any spoken phrase is its correctness. As a result of these factors, requirements for communication are created. We thought that during junior pupils’ speech improving the primary importance is work on language accuracy. Non-normative accents and speaking are often effect of negative impact of dialect environment on junior pupils. And this danger stores permanently.Іnformation technologies help to individualize and differentiate the studies of Ukrainian in initial classes. The uses of ICT do the lessons of Ukrainian and reading dynamic, bright, more effective. Improvement language culture for future primary school teacher is an integral part of the formation of his professiogram. Language environment is important factor for creating language culture. Dialect environment has both positive and negative influence. The worth-while experiment of the use of ICT at initial school we saw at Ivano-Frankivsk school №26. In spring in 2014 department of education entered in Ukraine a pedagogical experiment «Smart Kids». Within the framework of this experiment in the initial classes of school set projectors and interactive boards on that children execute educational tasks in a playing form. Games are a didactics, bright and interesting. So, regional dialects may do speech richer, but at the same time do it more complex: phonetically dialects are understandable by all speakers, however lexical are not understandable for people from another regions. Using dialects by students is natural phenomenon. This communication provides tight connection between history, way of life, customs of his native land.